Analysis of the Conformity of Productive Learning Competencies with the Implementation of Industrial Work Practices at SMK Negeri 3 Sinjai - A. Fina Destafiana; Nasaruddin Nasaruddin; Jamaluddin Jamaluddin (ASHA Publishing, 2024)
Analysis of the Suitability of Productive Learning Competencies with the Implementation of Industrial Work Practice for Automation and Office Management Students of SMK Negeri 3 Sinjai. This research was conducted with the purpose of this research to describe various aspects of the application of productive learning skills in relation to industrial work practices applied by SMK Negeri 3 Sinjai students in the field of automation and office management. The data in this qualitative research was collected through observation, interviews, and documentation. Five students of grade XI of SMK Negeri 3 Sinjai were used as research subjects. The suitability of the location with the student's study topic is an indication of the research findings. The first step in implementing industrial work practices is for schools to plan productive ability exams. The results of this study are seen in the suitability of the location placement with the student's field of study The process of implementing industrial work practices begins with planning by the school to test the productive ability of the subject matter with the field work material and industrial practice, even though the competencies possessed by students in the field of Automation and Office Management are in accordance with the needs of the industry, there are still challenges because some companies have not been able to offer jobs that match these skills. Based on the findings of this study, it is recommended that SMK Negeri 3 Sinjai strengthen coordination in establishing cooperation with the industrial sector to ensure the suitability of the field of work needed by the industrial world. With the implementation of prakerin, it is hoped that students will be able to get jobs that are in accordance with the skills and competencies they have mastered in the industrial world.